Hepatic alcohol dehydrogenase activity in alcoholic subjects with and without liver disease. Issue 6 (June 1990) - Vidal, F; Perez, J; Morancho, J; Pinto, B; Richart, C
Abstract : Alcohol dehydrogenase activity was measured in samples of liver tissue from a group of alcoholic and non-alcoholic subjects to determine whether decreased liver alcohol dehydrogenase activity is a consequence of ethanol consumption or liver damage. The alcoholic patients were classified further into the following groups: control subjects with no liver disease (group 1), subjects with non-cirrhotic liver disease (group 2), and subjects with cirrhotic liver disease (group 3). The non-alcoholic subjects were also divided, using the same criteria, into groups 4, 5, and 6, respectively. The analysis of the results showed no significant differences when mean alcohol dehydrogenase activities of alcoholic and non-alcoholic patients with similar degrees of liver pathology were compared (groups 1 v 4, 2 v 5, and 3 v 6. Alcohol dehydrogenase activity was, however, severely reduced in patients with liver disease compared with control subjects. Our findings suggest that alcohol consumption does not modify hepatic alcohol dehydrogenase activity. The reduction in specific alcohol dehydrogenase activity in alcoholic liver disease is a consequence of liver damage.